Public housing self-selection through user satisfaction in the City of Qom, Iran - Mahdi Torabi, 1974-, author (Johor Bahru, Johor : Universiti Teknologi Malaysia, 2018)
Thesis (Doktor Falsafah (Senibina)) - Universiti Teknologi Malaysia, 2018